LIPID EXTRACTION FROM MICROALGAE NANNOCHLOROPSIS SP. USING SWITCHABLE HYDROPHILICITY SOLVENTS - IRVA SARI (NIM : 20512030) ; Pembimbing Dr. Zeily Nurachman, Dr. Santi Nurbaiti, dan Dr.ir. D., MILA
Over the years, the price of fossil fuels has been steadily rising, which causes an increase of prices of food, consumer products, and transportation. Moreover, CO2 emissions related to the use of fossil fuels cause climate change. Therefore, renewable, carbon neutral and sustainable energy resources are required. Alternative energy sources derived from biomass, such as bio-based fatty acid methyl esters, are superior to fossil fuels as they are renewable, environmental friendly and of guaranteed availability. Microalgae, because of their high lipid productivity, could be the source of such bio-fuels. The extraction of lipids from microalgae is an energy intensive process. The application of switchable hydrophilicity solvents (SHSs) may offer advantages over more traditional methods of drying and extraction from the dried biomass. The switchable solvents offer the possibility to extract lipid material from wet microalgae slurries. Then, recover the lipids from extraction solvent by energy efficient phase separation after switching the hydrophilicity of the solvent by contacting it with CO2. In this study, the process of lipid extraction by using the solvents 2-(Dibutylamino)ethanol (DBAE) and 2-Ethyl-1-hexylamine (2EHA) from non-broken Nannochloropsis sp. was evaluated including the switching of the solvents, lipid extraction, and recovery of the leached solvent from the raffinate. The DBAE successfully switched to protonated DBAE after contacting with CO2 in about 100 minutes at 22Ã‚Â°C. It was found that more water increases the rate of switching the SHSs to their hydrophilic form. This switching is reversed by heating and N2 sparging. For 2EHA, on the other hand, the situation is less clear. Interestingly, upon switching with CO2, the sunflower oil forms a separate layer on top of respectively the 2EHA solvent and aqueous phase and can thus be recovered easily. In the lipid extraction, the solvent:algae slurry ratio and temperature were varied to investigated the effect on fatty acids yield and composition. For comparison, fatty vii acids were extracted by using the lab scale Bligh&Dyer extraction method. The extracted lipids were analyzed and showed C16:0, C16:1, C18:0, C18:1, and C20:5 fractions. The lipid extraction using DBAE was successful, with high lipid recycle (76 % wt., mainly C16:0 and C16:1). About 3.9 g/kg water phase of the DBAE losses to the algae slurry phase after lipid extraction. More than 98 % of the DBAE can be recovered easy using a heptane extraction of this water phase and the heptane can be evaporated to be separated from DBAE. And less than 1% of energy contained in the lipid extracted is required for this recovery process. The net DBAE loss is around 1 g DBAE per kg of lipids produced. The 2EHA lipid extraction from non-broken algae was not successful under the chosen conditions. More work in this area (new solvents and optimized process conditions) is still needed.